Pengaruh Penyajian dan Aksesibilitas Laporan Keuangan Desa terhadap Akuntabilitas Dana Desa - Neni Meilani; Edi Sukarmanto (Bandung Conference Series: Accountancy, 2022)
Abstract. This study aims to examine the effect of the presentation of village financial reports and the accessibility of village financial reports on the accountability of village funds in the villages of Cijaku and Malingping Districts, Lebak Regency. In this study, the sampling technique used by the researcher was purposive sampling with the criteria of the village secretary and finance officer. This type of research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect of the presentation of village financial reports and the accessibility of village financial reports on the accountability of village funds in the villages of Cijaku and Malingping Districts, Lebak Regency. This shows that if the Cijaku and Malingping sub-district governments in Lebak Regency present village financial reports properly and the accessibility of village financial reports is easy to obtain, it will increase the accountability of village funds for the Cijaku and Malingping sub-districts of Lebak Regency. Accountability is very necessary as an illustration that the organization is running well. Abstrak. Penelitian ini bertujuan untuk menguji pengaruh penyajian laporan keuangan desa dan aksesibilitas laporan keuangan desa terhadap Akuntabilitas dana desa di desa Kecamatan Cijaku dan Malingping Kabupaten Lebak. Dalam penelitian ini teknik pengambilan sampel yang digunakan oleh peneliti adalah purposive sampling dengan kriteria yaitu sekretaris desa dan kaur keuangan. Jenis penelitian ini merupakan penelitian kuantitatif. Teknik pengumpulan data menggunakan kuesioner. Teknik analisis data yang digunakan adalah analisis regresi linier berganda. Hasil penelitian ini menunjukkan adanya pengaruh yang positif dan signifikan dari penyajian laporan keuangan desa dan aksesibilitas laporan keuangan desa terhadap Akuntabilitas dana desa di desa Kecamatan Cijaku dan Malingping Kabupaten Lebak. Hal ini menunjukkan apabila Pemerintah Kecamatan Cijaku dan Malingping Kabupaten Lebak menyajikan laporan keuangan desa dengan baik serta aksesibilitas laporan keuangan desa mudah diperoleh maka akan meningkatkan Akuntabilitas dana desa Pemerintah Desa Kecamatan Cijaku dan Malingping Kabupaten Lebak. Akuntabilitas sangat diperlukan sebagai gambaran bahwa penyelenggaraan organisasi tersebut berjalan dengan baik.